Sodium Effects on the Diffusion, Phase, and Defect Characteristics of Kesterite Solar Cells and Flexible Cu2ZnSn(S, Se)4 with Greater than 11% Efficiency. (8th May 2021) - Yang, Kee‐Jeong; Kim, Sammi; Kim, Se‐Yun; Son, Dae‐Ho; Lee, Jaebaek; Kim, Young‐Ill; Sung, Shi‐Joon; Kim, Dae‐Hwan; Enkhbat, Temujin; Kim, JunHo; Kim, Juran; Jo, William; et al.
Abstract: Improving the efficiency of kesterite (Cu2 ZnSn(S, Se)4 ; CZTSSe) solar cells requires understanding the effects of Na doping. This paper investigates these effects by applying a NaF layer at various positions within precursors. The NaF position is important because Na produces Na‐related defects in the absorber and suppresses the formation of intrinsic defects. By investigating precursors with various NaF positions, the sulfo‐selenization mechanism and the characteristics of defect formation are confirmed. Applying a NaF layer onto a Zn layer in a CZTSSe precursor limits Zn diffusion and suppresses Cu‐Zn alloy formation, thus changing the sulfo‐selenization mechanism. In addition, the surface NaF layer provides reactive Se and S to the absorber layer by generating Na2 Se x and Na2 S x liquid phases during sulfo‐selenization, thus limiting the incorporation of Na into the absorber and reducing the Na effects. Efficiency values of 11.16% and 11.19% are obtained for a flexible CZTSSe solar cell by applying NaF between the Zn layer and back contact and between the Cu and Sn layers, respectively. This study presents methods for doping with alkali metals and improving the efficiency of photovoltaics. Abstract : Applying the NaF layer on a Zn layer in a CZTSSe precursor limits the diffusion of Zn and suppresses the formation of a Cu‐Zn alloy. An efficiency of 11.19% is obtained for the flexible CZTSSe solar cell by applying the NaF between the Cu and Sn layers.